Commodification of Content in the Soap Opera “Si Doel Anak Sekolahan” - Farah Laila Fazriah; Sigit Surahman; Yudhistira Ardi Poetra (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2023)
Commodification is the process of transforming use value into exchange value. The soap opera Si Doel Anak Sekolahan is the result of efforts to change from a use value that can entertain into an exchange value that brings financial benefits. These shows attract a large audience, which attractive to advertisers in various ways. This show is repeated every year from 2011 to 2023. This research uses a critical perspective by looking at the political economy of media. The concept of content commodification offered by Vincent Mosco became the scalpel for this research. Data for this study comes from the main source, namely the soap opera